Imaging in chronic posterior dislocation of the elbow: A rare entity - Reddy Ravikanth (Apollo Medicine)
The elbow is a complex joint, and traumatic dislocation of the elbow is the second most common major joint dislocation in adults more commonly occurring in athletes. Initial investigation of the suspected elbow dislocation includes radiographs in anteroposterior, lateral and oblique views. This case report describes chronic posterior dislocation in a 58-year-old woman and also describes the magnetic resonance imaging anatomy of the elbow joint. Timely intervention can alleviate symptoms and can prevent deformity and neurovascular sequelae.